2019
DOI: 10.1101/760033
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Odorant Receptor Inhibition is Fundamental to Odor Encoding

Abstract: Most natural odors are complex mixtures of many volatile components, competing to bind odorant receptors (ORs) expressed in olfactory sensory neurons (OSNs) of the nose. To date surprisingly little is known about how OR antagonism shapes neuronal representations in the periphery of the olfactory system. Here, we investigated its prevalence, the degree to which it disrupts OR ensemble activity, and its conservation across related ORs. Calcium imaging microscopy of dissociated OSNs revealed significant inhibitio… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…Beyond our theoretical observations, there are other more recent experimental studies (in bioRxiv preprints) that report related effects (Inagaki et al, 2019;Pfister et al, 2019;Xu et al, 2019). Our work is unique in the following regard:…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Beyond our theoretical observations, there are other more recent experimental studies (in bioRxiv preprints) that report related effects (Inagaki et al, 2019;Pfister et al, 2019;Xu et al, 2019). Our work is unique in the following regard:…”
Section: Discussionmentioning
confidence: 59%
“…Recent theoretical work has shown that a variety of non-linear interactions among multiple ligands at the same receptor can readily arise with a simple two-step model of receptor activation (Reddy et al, 2018). Experimental work in vitro in OSNs has suggested the existence of non-linear interactions, especially antagonism (Firestein and Shepherd, 1992;Kurahashi et al, 1994;Mathis et al, 2016;Rospars et al, 2008Rospars et al, , 2000Singh et al, 2019) (also bioRxiv preprints; Inagaki et al, 2019;Pfister et al, 2019;Xu et al, 2019). However, the prevalence of these interactions, especially in living animals within the constraints of natural sniffing dynamics, has not been explored.…”
Section: Introductionmentioning
confidence: 99%
“…All these lines of evidence support competitive antagonism as the most dominant form of modulation. In addition to partial agonism and synergetic and/or allosteric modulation we and others have reported, inverse antagonism in which high baseline activity in certain OSNs could be reduced by odorants (de March et al, 2020;Inagaki et al, 2020;Pfister et al, 2020;Zak et al, 2020).…”
mentioning
confidence: 67%
“…Consistent with our observations with SCAPE microscopy, several recent studies also demonstrated widespread modulation among odorants at the receptor level using various other techniques. These approaches include in vivo studies of dorsal OSNs (and glomeruli) in GCaMP3 mice with two-photon microscopy (Inagaki et al, 2019;Zak et al, 2020), identification of odorant receptors displaying odorant modulatory effects first in freely behaving mice (de March et al, 2020;McClintock et al, 2020) or in dissociated OSNs (Pfister et al, 2020) and then verification of the modulation effects in some of these odorant receptors with heterologous expression assays, as well as theoretical modeling predictions (Marasco et al, 2016;Reddy et al, 2018;Singh et al, 2019).…”
mentioning
confidence: 99%
“…In the context of mixtures, monomolecular odorants can act as agonists, antagonists, and partial agonists (Oka et al 2004, Rospars et al 2008, Takeuchi et al 2009) (Figure 2a). Indeed, most OR-ligand interactions are likely influenced by other monomolecular odors present in natural mixtures (Pfister et al 2019, Xu et al 2020. Furthermore, population-level OSN responses to natural stimuli are at least partially normalized in magnitude by competitive interactions between mixture constituents (Reddy et al 2018).…”
Section: Filtering the Olfactory Worldmentioning
confidence: 99%